Effect of organics with inorganic fertilizers on soil physico-chemical properties and enzymatic activities in rice-wheat cropping system - JAT, LOKESH KUMAR; DADHICH, S.K.; SINGH, HARPHOOL; SINGH, Y.V.; JATAV, HANUMAN SINGH; SETHI, INDUBALA; MALI, HANSRAM (Journal of Soil and Water Conservation, 2026)
Field experiments were conducted to assess the effects of combined application of organics with chemical fertilizers on soil physico-chemical properties and enzyme activities of soil in rice-wheat cropping system on Alluvial soils of Varanasi. The experiment was laid out in randomized block design (RBD) with nine treatments comprised of control (no fertilizer), 100% NPK and seven combinations of 70% NPK with different organics viz., FYM, pressmud and vermicompost, applied on nitrogen (N) basis. The result revealed that the substitution of 30% N through pressmud and FYM equally significantly lowered soil pH and improved soil electrical conductivity, organic carbon and cation exchange capacity. Application of 70% RDF + 30% N through FYM and pressmud also increased water holding capacity and reduced soil bulk density creating a good soil condition for enhanced growth of both crops. Application of 70% RDF + 30% N through FYM and pressmud recorded highest level of DTPA extractable Cu (2.73; 2.93 mg kg-1), Mn (13.28; 11.17 mg kg-1) and Zn (2.28; 2.44 mg kg-1), however, the highest DTPA extractable Fe (48.66; 43.59 mg kg-1) was recorded with application of 70% RDF + 30% N by FYM.